2005
DOI: 10.1007/s00213-005-0120-6
|View full text |Cite
|
Sign up to set email alerts
|

Anti-nociception is selectively enhanced by parallel inhibition of multiple subtypes of monoamine transporters in rat models of persistent and neuropathic pain

Abstract: Combined re-uptake inhibition of 5-HT and NA appears to confer a greater degree of anti-nociception in animal models of experimental pain than single mechanism of action inhibitors. The selective attenuation of mechanical allodynia by bupropion suggests that the additional re-uptake of DA may further augment 5-HT/NA re-uptake mediated anti-nociception after nerve injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
46
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(55 citation statements)
references
References 56 publications
3
46
5
Order By: Relevance
“…This is the first study to describe the antiallodynic effects of nalbuphine in nonhuman primates, although nalbuphine was shown to be effective in some rat models of inflammatory pain (Lomas et al, 2007;Ortiz et al, 2007;Ortiz and Castañ eda-Herná ndez, 2008). Clomipramine produced little or no effect up to the highest dose tested in all three assays, which agrees with previous studies in finding that clomipramine and other serotonin uptake inhibitors produce little effect on rates of schedule-controlled responding or thermal nociception in nonhuman primates (Kleven and Woolverton, 1993;Spealman, 1993;Gatch et al, 1998) or pain-related behaviors in rodent models of inflammatory pain (Pedersen et al, 2005).…”
Section: Discussionsupporting
confidence: 84%
“…This is the first study to describe the antiallodynic effects of nalbuphine in nonhuman primates, although nalbuphine was shown to be effective in some rat models of inflammatory pain (Lomas et al, 2007;Ortiz et al, 2007;Ortiz and Castañ eda-Herná ndez, 2008). Clomipramine produced little or no effect up to the highest dose tested in all three assays, which agrees with previous studies in finding that clomipramine and other serotonin uptake inhibitors produce little effect on rates of schedule-controlled responding or thermal nociception in nonhuman primates (Kleven and Woolverton, 1993;Spealman, 1993;Gatch et al, 1998) or pain-related behaviors in rodent models of inflammatory pain (Pedersen et al, 2005).…”
Section: Discussionsupporting
confidence: 84%
“…In contrast to both tricyclic antidepressants, venlafaxine did not reverse thermal hyperalgesia, but attenuation of allodynia was observed at all of the time points with statistical significance measured only at the highest dose (25 mg). This result is inconsistent with the results obtained in 2005 by Pedersen et al [43] in which venlafaxine was ineffective against mechanical allodynia in CCI and spinal nerve ligation models. This study also reported that venlafaxine transiently increased the tail-flick latency in uninjured animals and attenuated second-phase flinching in the formalin test in rats [43].…”
Section: Discussioncontrasting
confidence: 99%
“…This result is inconsistent with the results obtained in 2005 by Pedersen et al [43] in which venlafaxine was ineffective against mechanical allodynia in CCI and spinal nerve ligation models. This study also reported that venlafaxine transiently increased the tail-flick latency in uninjured animals and attenuated second-phase flinching in the formalin test in rats [43]. Interestingly, Lang et al [21] has shown that venlafaxine administered per os in the CCI model prevented the development of chronic pain if it was administered before the constriction to the sciatic nerve and reversed pain if it was given after, which is in agreement with our results.…”
Section: Discussioncontrasting
confidence: 99%
“…Dual NET and SERT inhibitors, such as the tricyclic antidepressants (TCAs) amitriptyline and desipramine (Owens et al, 1997), possess greater analgesic efficacy, particularly in painful neuropathic states such as herpes neuralgia, diabetic neuropathy, and nerve crush syndromes (Sindrup et al, 2005), than either selective NET or SERT inhibitors (Fishbain et al, 2000). Likewise, the contribution of dopaminergic pathways to analgesic processes is supported by observations that dopamine transport (DAT) inhibitors (Pedersen et al, 2005) and D 2 agonists (Magnusson and Fisher, 2000) are antinociceptive in models of acute and chronic pain elicited by a number of modalities. Clinical evidence of a role for DA in modulating nociceptive inputs is provided by the hyperalgesia associated with dopaminergic hypofunction, such as in Parkinson's disease (Drake et al, 2005), whereas the DAT inhibitor bupropion (Semenchuk and Davis, 2000) and the DA precursor levodopa (Ertas et al, 1998) are analgesic in neuropathic pain syndromes (Hagelberg et al, 2004).…”
mentioning
confidence: 99%
“…Dual uptake inhibitors, such as venlafaxine and duloxetine, which are clinically effective in reducing neuropathic pain (Lang et al, 1996;Iyengar et al, 2004), have mitigated many of these limiting side effects. However, enhancement of dopaminergic neurotransmission may further expand the favorable analgesic profile of dual NET and SERT inhibitors (Pedersen et al, 2005). To this end, we have characterized the antinociceptive properties of bicifadine (1-p-tolyl-3-azabicyclo[3.1.0]hexane), an inhibitor of biogenic amine transporters, in animal models of acute and chronic pain.…”
mentioning
confidence: 99%